Targeted Delivery of Auristatin-Modified Toxins to Pancreatic Cancer Using Aptamers - Christina Kratschmer; Matthew Levy (Elsevier, 2018)
Pancreatic cancer is one of the most lethal malignancies. Treatment with the first-line agent, gemcitabine, is often unsuccessful because it, like other traditional chemotherapeutic agents, is non-specific, resulting in off-target effects that necessitate administration of subcurative doses. Alternatively, monomethyl auristatin E (MMAE) and monomethyl auristatin F (MMAF) are highly toxic small molecules that require ligand-targeted delivery. MMAE has already received FDA approval as a component of an anti-CD30 antibody-drug conjugate, brentuximab vedotin. However, in contrast to antibodies, aptamers have distinct advantages. They are chemicals, which allows them to be produced synthetically and facilitates the rapid development of diagnostics and therapeutics with clinical applicability. In addition, their small size allows for enhanced tissue distribution and rapid systemic clearance. Here, we assayed the toxicity of MMAE and MMAF conjugated to an anti-transferrin receptor aptamer, Waz, and an anti-epidermal growth factor receptor aptamer, E07, on the pancreatic cancer cell lines Panc-1, MIA PaCa-2, and BxPC3. In vitro, our results indicate that these aptamers are a viable option for the targeted delivery of toxic payloads to pancreatic cancer cells.